Quality Management in Islamic High School Education: A Case Study: Manajemen Kualitas dalam Pendidikan Sekolah Menengah Islam: Studi Kasus - Najah, Latifatun; Catur Wahyuni, Hana (Adabiyah: Jurnal Pendidikan Islam, 2025)
General Background: Quality management in Islamic education is crucial for ensuring effective learning outcomes and institutional development. Specific Background: Madrasah Aliyah Muhammadiyah 1 Paciran, as a leading Islamic high school, applies input–process–output management but faces challenges in maintaining consistent standards. Knowledge Gap: Limited studies have deeply explored how Islamic secondary schools address obstacles in quality management through practical strategies. Aims: This research aims to analyze the obstacles, solutions, and indicators of quality management at MA Muhammadiyah 1 Paciran. Results: The study, using descriptive qualitative methods through observation and interviews, reveals that input challenges include detailed planning in student admission (PPDB), process challenges involve teachers’ limited use of PAIKEM and IT skills, while output challenges are related to students’ inconsistent engagement in follow-up programs. Solutions include structured TUPOKSI in PPDB, continuous teacher training, IT-based learning media, and institutional motivation programs. Novelty: This study emphasizes integrated solutions combining administrative detail, pedagogical strategies, and technological adaptation within an Islamic education context. Implications: Findings highlight the importance of structured management and innovation in Islamic high schools to strengthen student outcomes and institutional competitiveness. Highlights: Identifies obstacles in input, process, and output management. Provides practical solutions for teacher capacity and IT integration. Offers insights for strengthening Islamic high school quality. Keywords: Quality Management; Input-Process-Output; Islamic Education; Madrasah; Secondary School